European integration and cooperation, basic vectors of European space of freedom, security and justice - Ion Balaceanu; Mihaela-Flavia Din (Hyperion Economic Journal, 2013)
European integration and cooperation, basic vectors of European space of freedom, security and justiceAbstract: The European countries joining to the Schengen area had the effect elimination of internal border controls between Schengen member countries, that use permenent provisions of the Schengen acquis, being a single external border where operational checks are carried out according to a set of clear rules on immigration, visas, the asylum, as well as some decisions concerning police cooperation, judicial or customs. This means that the border crossing can be made at any time through many places, and citizens of member countries who are traveling in the Schengen area must present a valid ID. Overcoming internal border can be equated with a journey through the country.